2011
DOI: 10.1029/2010ja015949
|View full text |Cite
|
Sign up to set email alerts
|

The 762 nm emissions of sprites

Abstract: [1] We report the 762 nm emissions in sprites recorded by the ISUAL experiment onboard the FORMOSAT-2 satellite. The 762 nm imager filter is centered at 763.3 nm with a 7 nm bandwidth at 50% transmittance. Sprite emissions in this passband include the N 2 first positive (1PN 2 ) bands, (2, 0) and (3, 1), the O 2 atmospheric (atm) band (0, 0), and the hydroxyl (4, 0) emissions. Because these mixed emissions cannot be resolved in the 762 nm narrowband filter, a zero-dimensional plasma chemistry model is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Kuo et al adopted the Sentman kinetic scheme but include a few corrected chemical processes for a similar but independent plasma chemistry study of TLEs. Kuo et al (Kuo et al, 2011) found that the modelling intensity ratios N 2 1P/N 2 2P, N 2 + 1N/N 2 2P were in good agreement with ISUAL optical measurements. Moreover, they also reported, for the first time, the evidence for the existence of O 2 atmosphere (0-0) band in sprites that was predicted by the plasma chemistry model (Sentman et al, 2008;Sentman & Stenbaek-Nielsen, 2009).…”
Section: Full Kinetic Scheme In Discharge Gassupporting
confidence: 70%
“…Kuo et al adopted the Sentman kinetic scheme but include a few corrected chemical processes for a similar but independent plasma chemistry study of TLEs. Kuo et al (Kuo et al, 2011) found that the modelling intensity ratios N 2 1P/N 2 2P, N 2 + 1N/N 2 2P were in good agreement with ISUAL optical measurements. Moreover, they also reported, for the first time, the evidence for the existence of O 2 atmosphere (0-0) band in sprites that was predicted by the plasma chemistry model (Sentman et al, 2008;Sentman & Stenbaek-Nielsen, 2009).…”
Section: Full Kinetic Scheme In Discharge Gassupporting
confidence: 70%
“…[]. For a more detailed analysis of the temporal evolution of excited bands, we consider the zero‐dimensional models: the (C) simple analytic model and the (D) plasma chemistry model [ Sentman et al ., ; Sentman and Stenbaek‐Nielsen , ; Kuo et al ., ; Kuo et al ., ] with different applied reduced electric field, E / N , where E is the electric field and N is ambient neutral density. We want to know a reasonable magnitude of the reduced electric field in the halo region for the reported halo event.…”
Section: Resultsmentioning
confidence: 99%
“…For the (D) plasma chemistry model at halo altitude of 80 km, we apply the magnitudes of electric field from 150 Td to 350 Td with every step 50 Td to obtain the ratios of N 2 + 1N to N 2 2P for τ E = 0.1, 0.3, 0.5 ms. The plasma chemistry model was adopted using the kinetic scheme [ Sentman et al ., ; Kuo et al ., ; Kuo et al ., ]. In this scheme, chemical reactions associated with N 2 ( C 3 ∏ u ) are initially dominated by the electron‐impact process, e+normalN2e+normalN2C3u,and, for longer time scales, N 2 ( C 3 ∏ u ) can be excited via the collisional activation reaction with normalN2normalA3normalu+ [ Sentman et al ., ], normalN2A3u++normalN2A3u+normalN2C3u.…”
Section: Resultsmentioning
confidence: 99%
“…The ensuing transient electric field accelerates and injects energy into electrons causing them to collide with molecular nitrogen and molecular oxygen, inducing excitation and/or ionization, and eventually resulting in the expanding donut‐shape luminous emissions near the lower ionosphere. The typical brightness of an elve is lower than the other types of TLEs in the ISUAL observations [ Kuo et al , 2005; Mende et al , 2005; Su et al , 2005; Adachi et al , 2006; Liu et al , 2006; Frey et al , 2007; Kuo et al , 2007; Adachi et al , 2008; Chen et al , 2008; Kuo et al , 2008, 2009; Chang et al , 2010; Chou et al , 2010; Huang et al , 2010; Lee et al , 2010; Kuo et al , 2011]. In addition, the luminous duration of elve emissions is shortest (<1 ms) among the known species of TLEs.…”
Section: Introductionmentioning
confidence: 92%